PENGEMBANGAN MEDIA MAGNETIC PUZZLE MUATAN SISTEM PENCERNAAN SISWA KELAS V SD NEGERI 72 PALEMBANG - Nayaki, Calista Poethy; Sholeh, Kabib; Syaflin, Sylvia Lara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students' difficulties in understanding the material in IPAS subjects, especially in abstract material, as well as the lack of utilization of learning media on abstract material, are the background of this research. With this background, this research aims to make it easier for students to understand the material. This study aims to produce magnetic puzzle media that is valid and practical. The method used in this research is the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The ADDIE model is one of the models in developing a product so that it can be used in the learning process. The results of this study show that students' needs for learning media with an average of three indicators of material difficulty, learning media needs and learning methods obtained a percentage of 73.94%. And three aspects to assess the validity, namely the validity of the media, material and language with a validity value of 88.63% which shows a very valid category. Followed by a one to one evaluation trial which obtained a practicality value of 90.66% and a small group evaluation trial which received a value of 90.2% with a very practical category. Therefore, the development of magnetic puzzle media can be declared valid and practical.